Dialogue as a Resource: Psychological Support for Adolescents in the Context of Traumatic Experience - Nauchitel, Olena; Kharchenko, Andriy; Yakusheva, Yevheniia (Psychological Counseling and Psychotherapy, 2025)
Problem definition. In the current socio-political context resulting from military actions on the territory of Ukraine, the issue of psychological support for adolescents has become exceptionally urgent. The psychological trauma experienced by teenagers in wartime conditions is a complex and multifaceted phenomenon that affects emotional stability, levels of social adaptation, academic motivation, and the development of life orientations. Unlike adults, adolescents do not yet possess sufficient resources to cope independently with traumatic events; therefore, particular attention must be paid to developing effective methods of psychological support for this age group. Despite the existence of numerous studies on traumatic experiences, the issue of providing effective psychological assistance to adolescents who are under emotional stress due to war remains insufficiently explored both theoretically and practically. There is a need for further development of innovative means of overcoming psychological trauma that are based on a combination of external dialogue between the psychologist and the adolescent and internal dialogue—in the form of interaction with an imagined interlocutor. Dialogue, as a foundation of therapeutic engagement, may become a resource that opens possibilities for internal restoration, reflection, the actualization of emotional experiences, and gradual integration of traumatic events into one’s personal life narrative. The relevance of this issue is determined not only by the quantitative increase in psychological support requests but also by the ongoing nature of the war, which gives traumatic experiences a prolonged character and affects personality development in conditions of sustained turbulence. Accordingly, there arises a need for theoretical reflection on the potential of dialogue as a support instrument, as well as the exploration of applied aspects of psychological counseling for adolescents in crisis. In this context, direct interaction with the therapeutic toy Hibuki and its symbolic image contributes to the creation of a safe emotional space that enables adolescents to express complex emotional experiences, reframe traumatic memories, and discover internal psychological support.